Systemic Juvenile Idiopathic Arthritis–like Syndrome in Mice Following Stimulation of the Immune System With Freund's Complete Adjuvant: Regulation by Interferon‐γ. Issue 5 (May 2014) - Avau, Anneleen; Mitera, Tania; Put, Stéphanie; Put, Karen; Brisse, Ellen; Filtjens, Jessica; Uyttenhove, Catherine; Van, Jacques; Liston, Adrian; Leclercq, Georges; Billiau, An D.; Wouters, Carine H.; et al.
<x xml:space="preserve">Abstract</x> Objective Systemic juvenile idiopathic arthritis (JIA) is unique among the rheumatic diseases of childhood, given its distinctive systemic inflammatory character. Inappropriate control of innate immune responses following an initially harmless trigger is thought to account for the excessive inflammatory reaction. The aim of this study was to generate a similar systemic inflammatory syndrome in mice by injecting a relatively innocuous, yet persistent, immune system trigger: Freund's complete adjuvant (CFA), containing heat‐killed mycobacteria. Methods Given the central role of interferon‐γ (IFNγ) in immune regulation, we challenged wild‐type (WT) and IFNγ‐knockout (KO) BALB/c mice with CFA, and analyzed their clinical symptoms and biologic characteristics. The production of cytokines and the effects of anticytokine antibodies were investigated. Results In WT mice, CFA injection resulted in splenomegaly, lymphadenopathy, neutrophilia, thrombocytosis, and increased cytokine expression. In the absence of IFNγ, these symptoms were more pronounced and were accompanied by weight loss, arthritis, anemia, hemophagocytosis, abundance of immature blood cells, and increased levels of interleukin‐6 (IL‐6), all of which are reminiscent of the symptoms of systemic JIA. CFA‐challenged IFNγ‐KO mice showed increased expression of IL‐17 by CD4+ T cells and by innate γ/δ T cells. Inflammatory and hematologic changes were prevented by treatment with anti–IL‐12/IL‐23p40 and anti–IL‐17 antibodies. Conclusion Immune stimulation of IFNγ‐KO mice with CFA produces a systemic inflammatory syndrome reflecting the clinical, biologic, and histopathologic picture of systemic JIA. The protective function of IFNγ in preventing anemia and overall systemic inflammation is a striking observation. The finding that both adaptive and innate T cells are important sources of IL‐17 may be of relevance in the pathogenesis of systemic JIA.